2012
DOI: 10.1002/clen.201100322
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene Removal from Aqueous Solution on Sesame Stalk‐based Carbon

Abstract: This work explored the performance of sesame stalk-based carbon prepared at different carbonization temperatures and activated by potassium hydroxide in the removal of phenanthrene from an aqueous solution. At a carbon concentration of 10 mg/32 mL and a carbonization temperature of 7008C, the removal efficiency of phenanthrene approached 100%. Furthermore, with the presence of acenaphthene and naphthalene as co-contaminants, the removal efficiency of phenanthrene by the prepared carbon was 99.60%, which was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…In recent years, biochar production, focused on agricultural residues, has gained increasing interest [1][2][3]. Biochar is a recalcitrant organic compound and better environmental improvement additive, created when biomass (feedstock) is heated to temperatures between 300 and 10008C under low oxygen concentrations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biochar production, focused on agricultural residues, has gained increasing interest [1][2][3]. Biochar is a recalcitrant organic compound and better environmental improvement additive, created when biomass (feedstock) is heated to temperatures between 300 and 10008C under low oxygen concentrations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The last principal factor of lignocellulose which decides sorption capacity is surface morphology (topographical and elemental information) (Kong et al, 2012). Scanning Electron Microscope (SEM) is the method was often utilized to determine this characterization.…”
Section: Lignocellulosementioning
confidence: 99%
“…Sesame stalk-based carbon was used for removing phenanthrene from water by Kong et al (2012). The biosorbent was prepared from sesame stalk by carbonization with temperature 300°C, 400°C, 500°C, 600°C, 700°C and impregnation with KOH solution.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of carbon-based absorbents can be greatly enhanced by treatment of the carbon with certain chemicals, either initially or before a final activation stage. Potassium hydroxide is one of the most widely studied activating agents (Wu et al 2005;Radhika and Palanivelu 2006;Tan et al 2008;Kilic et al 2011;Wu et al 2011Wu et al , 2012bKong et al 2012). Radhika and Palanivelu (2006) found that KOH-activated carbon outperformed products that they prepared from five other activating systems relative to sorption of chlorophenol.…”
Section: Activating Compoundmentioning
confidence: 99%